Path Planning for Nonholonomic Mobile Robot Based on Bezier Curve - Kavuran, Gurkan (Ieee, 2017)
This study presents simulation results of nonholonomic mobile robot control with path planning which is based on Bezier Curves. The purpose of this paper is set to develop a simulation model for differential drive wheeled (DDW) robot by using MATLAB/Simulink environment. Fractional order PID structure is used to increase the tracking performance of DDW robot. Simulation results are compared for the various path scenario. It was shown that the proposed control scheme exhibits agreeable performance for the desired path tracking.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Mobile robot; path planning; Bezier curves; fractional order control; simulation